Effects of a directional abiotic gradient on plant community dynamics and invasion in a coastal dune system - LORTIE, CHRISTOPHER J; CUSHMAN, J. HALL (The Journal of ecology, 2007)
1 Local abiotic factors are likely to play a crucial role in modifying the relative abundance of native and exotic species in plant communities. Natural gradients provide an ideal opportunity to test this hypothesis. 2 In a coastal dune system in northern California, we used comparative and experimental studies to evaluate how a wind and soil texture gradient influences the relative abundance of native and exotic plant species in this community. 3 We detected small-scale spatial variation in soil texture along a 200-m gradient from relatively sheltered to more exposed. Sand coarseness significantly increased with exposure while soil nitrate levels significantly decreased. The more extreme end of the gradient was also subject to greater wind speeds and less soil moisture. 4 The plant community consistently responded to this gradient in the 7 years censused. Species richness decreased with exposure, cover of natives decreased and cover of exotics increased at the more extreme end of the gradient. 5 A single-season wind-shelter experiment similarly shifted the balance between native and exotic species. Shelters decreased the relative density of exotic species and increased the relative density of natives regardless of position on the gradient. 6 These comparative and manipulative findings both suggest that a single factor, wind, at least partially explains the success of exotic species in a coastal dune plant community. This supports the hypothesis that local abiotic conditions can explain differences in invasibility within a plant community.